The cathepsin-D expression in the cyto-invasive stages of coccidia in intestinal mucosa of chickens, and the relevance of this proteinase for intracellular penetration and spreading of coccidia in host tissues - Koďousek, Rostislav; Bedrník, Petr; Černík, František; Kubeš, Oldřich (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2001)
The Cathepsin-D proteinase was demonstrated immunohistochemically in cases of intestinal coccidiosis in chickens; its expression concerned almost the cyto-invasive stages of reproductive cycle of several strains of coccidia (merozoites of the II-nd generation and also microgametes). The authors consider Cathepsin-D as a potentional "penetration/spreading factor", being significant for intracellular invasion and spreading of coccidia into host cells. In diagnostic practice, an immunohistochemical demonstration of Cathepsin-D is a relatively simple and sensitive method, which brings information on the extent of parasitic lesions, and on participation of particular evolutive forms of coccidial life cycle; it may also be useful in proving isolated coccidia in the intestinal epithelium, poorly recognized in routine HE preparation. Some Cathepsin-D protease reactivity in intestinal Cryptosporidiosis is also briefly mentioned. The examined cases of cerebral toxoplasmosis and primary acanthamoebic meningoencephalitis (PAME) showed in above mentioned methods negative results.
Keywords: kur domácí; Coccidiosis; Poultry Diseases; zvířata; nemoci drůbeže; střevní sliznice; Animals; imunohistochemie; Immunohistochemistry; Cathepsin D; kathepsin D; kokcidióza; Intestinal Mucosa; Chickens